Alto estrutural na região de Laranjal Paulista/SP: caracterização gravimétrica e geológica - Montanheiro, Mariana Aparecida Fernandes [UNESP] (2015)
Studies involving gravimetric surveys at regional scale, allied to geological/structural recognition, consist the fundamental principle to elaborate geological modeling supported by gravimetric data, providing important elements for characterization of sedimentary basins. In this manner the goal of the present study, considering from gravimetric anomalies, is to recognize the tectonic evolution occurred in the region of Laranjal Paulista, from the central portion of São Paulo state. It was already known in this region the occurrence of a part of a significant positive gravimetric anomaly. The high contrast between the values of the anomaly and the regional coverage of this feature was the reason of interest in developing this study, applying gravimetric method to explain the geological/structural scenario in which is inserted. Thus, to meet the goal proposed, it was necessary to delimitate and to prove the existence of the gravimetric anomaly through a series of steps which were result of the development of gravimetric models and that showed the existence of a high structural in the region, bounded by tectonic lineaments of the basement which were reactivated and originated this feature. As were identified tectonic-stratigraphic evidences in the geological map of the region, that suggest the existence of a high basement structuring the Paleozoic rocks, it is understood that the same has originated after the deposition of that rocks, at least in the Mesozoic